Pancreatic Islet Changes in Human Whole Organ Pancreas Explants: What Can Be Learned From Explanted Samples?. Issue 11 (November 2020) - Dumbill, Richard; Laurenson-Schafer, Hannah; Sharples, Edward J.; Barnes, James; Mittal, Shruti; Friend, Peter J.; Clark, Anne
Abstract : Background: Whole pancreas transplantation (Tx) is a successful treatment for type 1 diabetes resulting in independence from antidiabetic therapies. Transplant-related factors contributing to pancreatic islet failure are largely unknown; both recurring insulitis and pancreatitis have been implicated. The aim was to determine if cellular changes in islets and exocrine tissue are evident early in Tx, which could contribute to eventual graft failure using well-preserved tissue of grafts explanted from largely normoglycemic recipients. Methods: Histological specimens of explants (n = 31), Tx duration 1 day–8 years (median 29 d), cold ischemia time 7.2–17.3 hours (median 11.1 h), donor age 13–54 years (median 38 y) were examined; sections were labeled for inflammation, islet amyloidosis, and tissue fibrosis, and morphometry performed on immunolabeled insulin and glucagon positive islet cells. Data were related to clinical details of donor, recipient, and features of Tx. Results: Islet inflammation consistent with recurrent insulitis was not seen in any sample. Insulin-labeled islet cell proportion decreased with donor age ( P < 0.05) and cold ischemia ( P < 0.01) in explants from 26 normoglycemic patients; glucagon-labeled area proportion increased with cold ischemia ( P < 0.05). Clinical pancreatitis was the explant reason in 12 of 28 normoglycemic cases. Exocrine fibrotic area/pancreas was variable (0.7%–55%) and unrelated to clinical/pathological features. Islet amyloid was present in 3 normoglycemic cases (donor ages 58, 42, and 31 y; Tx duration 8 y, 31 and 33 d, respectively). In 1 patient receiving antidiabetic therapy, the insulin-labeled area was reduced but with no evidence of islet inflammation. Conclusions: Explant histological changes after short-term Tx are similar to those seen in type 2 diabetes and occur in the absence of immunologic rejection without causing hyperglycemia. This suggests that factors associated with Tx affect islet stability; persistent deterioration of islet integrity and exocrine tissue fibrosis could impact on sustainability of islet function.